Effects of Hull Inclusión in Diets for Rabbits - Trigo, María Soledad (2014)
Improving efficiency of digestion and use of balanced diets is one of the challenges ahead, both to improve the health conditions of animals and to design production systems compatible with the environment. The aim of this work was to study the effect of the addition of hull to the diet of meat rabbits on days to slaughter, on mortality in the fattening period and N (nitrogen) and P (phosphorous) percentages excreted in feces. 64 rabbits were used weaned at 28 days. They were fed ad libitum. Diets consisted of two commercial formulations (Ga and Ge) with and without husk of wheat and oats by 10% (P / P). Time of fattening and mortality was recorded for each diet. Feces were collected from 48 cages at the beginning and end of fattening (45 and 65 days) and percentage of NT (total nitrogen) was determined by micro-Kjeldahl and TP (total phosphorus) by colorimetry with metavanadate. The animals fed with husks in the diet showed a higher slaughter age and mortality decrease. The only factor tested that caused significant differences in nitrogen excretion was the addition of hull. The oat hull diet showed a significantly lower nitrogen removal. Phosphorus excretion showed a significant difference according to the type of commercial diet fed, the addition of husk and the fattening stage. While adding outside fiber to food causes a delay in the time of slaughter, this would be partially offset by a reduction in mortality. The addition of oat hulls would be a viable alternative to reduce emissions of nitrogen and phosphorus to the environment via feces.